Molecular Characterization of Malignant Renal Epithelioid Angiomyolipoma: A Review of Two Cases. Issue 3 (20th January 2023) - Rammal, Rayan; Korentzelos, Dimitrios; Skaugen, John M; Quiroga-Garza, Gabriela M
Abstract: Objectives: Epithelioid angiomyolipoma (EAML, perivascular epithelioid cell tumor) is an uncommon primary renal tumor that may recur or metastasize, although there remain limited data for prediction of these outcomes. Here, we report two cases of renal EAML with molecular testing, adding to the existing literature of potential alterations associated with malignant behavior. Methods: Tumors diagnosed as malignant renal EAML were identified, and clinical data, radiology, histology, immunohistochemistry, and molecular testing results were reviewed. Results: Two cases of malignant renal EAML were identified, both of which demonstrated TSC2 and TP53 mutations. In ATRX, one had a mutation and the other had a variant of uncertain significance. In addition, one patient had a synchronous classic angiomyolipoma that lacked TP53 and ATRX alterations. Conclusions: These findings highlight the molecular landscape of malignant renal EAML and expand on the existing literature suggesting a role for TP53 and ATRX alterations in malignant progression of these tumors. The presence of synchronous benign and malignant tumors within the same patient offers a unique opportunity to directly compare the molecular alterations, further supporting the association with aggressive behavior.